Green Synthesis and Characterization of 4'-Hydroxy-4-Nitro Chalcone using Grinding Techniques - Elfi Susanti VH; Sri Retno Dwi Ariani; Sri Mulyani; Suryadi Budi Utomo; Muhammad Hizbul Wathon (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The challenge of developing environmentally friendly synthesis methods for biologically active compounds remains a significant focus in green chemistry. This study aimed to synthesize 4'-hydroxy-4-nitro chalcone from 4-hydroxyacetophenone and 4-nitrobenzaldehyde using a grinding technique and then characterize the synthesized compounds. The 4'-hydroxy-4-nitro chalcone was synthesized via the Claisen-Schmidt grinding method for 45 minutes at room temperature. The grinding results were extracted with chloroform. The formed crystals were tested for purity by thin-layer chromatography (TLC), and further purification was carried out by recrystallization. The synthesized chalcone was characterized using FTIR, 1H-NMR, and 13C-NMR  spectroscopy. The chalcone was also tested for antibacterial activity using the disc diffusion method against Staphylococcus aureus and Escherichia coli. The results showed that 4'-hydroxy-4-nitro chalcone could be successfully synthesized from 4-hydroxyacetophenone and 4-nitrobenzaldehyde using the grinding technique, yielding orangish-white crystals with a 70.63% yield and a melting point of 173°C. Purity was confirmed by TLC, and structural characterization was achieved through FTIR, 1H-NMR and 13C-NMR spectroscopy. Antibacterial testing revealed that the synthesized chalcone produced a clear zone diameter of 9.27 mm against S. aureus and 27.88 mm against E. coli. These results indicate that the compound has relatively strong antibacterial activity against E. coli and relatively weak activity against S. aureus. This study demonstrates the effectiveness of the green synthesis method and provides valuable insights into the antibacterial properties of 4'-hydroxy-4-nitro chalcone